Learning through the experience of cancer survivorship: differences across age groups. Issue 4 (13th July 2021) - Bilodeau, Karine; Lee, Virginia; Pepin, Jacinthe; Pomey, Marie-Pascale; Sultan, Serge; Folch, Nathalie; Charpentier, Danielle; Vachon, Marie-France; Dumont-Lagacé, Élise; Piché, Lynda
Abstract: Objective: To identify and describe challenges that contribute to experiential learning among cancer survivors across different age groups. Research approach: Qualitative collaborative study Participants: 27 cancer survivors Methodological approach: Participants were invited to explain the after-cancer challenges they learned from during six focus groups. Five were organized by age-group (15-18, 19-34, 35-44, 45-59, ≥ 60) and a mixed group was held to ensure the co-construction of findings with participants. Inductive content analysis was performed. Findings: While learning to live with a chronic disease, participant's experiential learning appeared through four challenges: Searching for one's identity, Autonomy, Disruption of social roles and responsibilities, Reclaiming one's life. Particular aspects of challenges were identified across ages-groups and life courses. Interpretation: Results indicate that psychosocial and health professionals should be sensitive to the fact that life courses are now diverse and not always associated with biological age. This has the potential to improve care by informing how these challenges affect the experience of cancer survivorship over time.